Clinical features of hepatitis B and C virus infections, with high α-fetoprotein levels but not hepatocellular carcinoma. Issue 2 (January 2017) - Kim, Cha Young; Kim, Bo Ra; Lee, Sang Soo; Jeon, Dae-Hong; Lee, Chang Min; Kim, Wan Soo; Cho, Hyun Chin; Kim, Jin Joo; Lee, Jae Min; Kim, Hong Jun; Ha, Chang Yoon; Kim, Hyun Jin; et al.
Abstract : Abstract: The appropriate α-fetoprotein (AFP) level to confirm hepatocellular carcinoma (HCC) could be 100 ng/mL; however, the clinical significance of falsely elevated AFP in patients without HCC has not been fully studied. We investigated the clinical features and outcome of patients without HCC but with high AFP levels (100 ng/mL), especially with chronic hepatitis B (CHB) or C (CHC). The sample included 124 consecutive patients with CHB (n = 97) or CHC (n = 27), with AFP levels >100 ng/mL and without HCC at baseline. Multivariate Cox proportional regression analysis was performed to determine the factors associated with AFP normalization and HCC development. During the mean 52-month follow-up, the proportion of patients with CHB with AFP normalization (90.7%) was significantly higher than the proportion of patients with CHC (59.3%, P  < 0.001). Initial aspartate aminotransferase levels (hazard ratio [HR] = 1.02 per 10 U/L increase, P  = 0.021) and antiviral therapy (HR = 2.89, P  < 0.001) were significantly associated with AFP normalization. Of the 16 (12.9%) patients who developed HCC, hepatitis B virus infection (HR = 10.82, P  = 0.001), initiation of antiviral treatment postenrollment (HR = 0.23, P  = 0.030), and AFP normalization within 12 months (HR = 0.13, P  = 0.011) were associated with HCC development. CHB and CHC were the most common causes of falsely elevated AFP (>100 ng/mL). With either CHB or CHC, persistent AFP elevation (>12 months), regardless of antiviral treatment, might be an important marker of HCC development. Abstract : Supplemental Digital Content is available in the text